Happy New Year! - Ackelsberg, Amy; Thomas, Laura (Laura Dianna) (New York, New York : Grosset & Dunlap, an imprint of Penguin Group (USA) LLC, 2014)
"Strawberry Shortcake and her friends are berry excited for New Year's Eve -- everyone except Blueberry Muffin, that is! While the rest of the girls are busy preparing for Strawberry's festive holiday bash, Blueberry is worried that she won't be able to stay up until midnight to ring in the New Year with her friends. Will Blueberry make it until the clock strikes twelve? Or will she have the berry worst New Year's Eve ever?"--Page [4] of cover.
At head of title: Strawberry Shortcake.
"Sweet stickers inside!"--Cover.
Ages 3 and up.
Ages 3 and up.
Keywords: Strawberry Shortcake (Fictitious character) -- Juvenile fiction; New Year -- Juvenile fiction; Parties -- Juvenile fiction; Friendship -- Juvenile fiction; friendship; New Year; Parties; Strawberry Shortcake (Fictitious character); Fiction; Juvenile works